2017
DOI: 10.16965/ijpr.2017.216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerobic Exercises on Iron Deficiency Anemia in Girls

Abstract: Background: Iron deficiency anemia has recently been ranked as the third leading cause worldwide of loss of disability-adjusted life years for women aged from 15 to 44 years.Objectives: This study was conducted to determine the effect of aerobic exercises on anemia in girls. Participants and methods:Thirty girls participated in this study, their age ranged from 17 to 22 years. They were divided randomly into two groups equal in number: Study group (group A) performed aerobic exercises in form of bicycling (60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Menstrual disorders not only affect daily activities and quality of life but are also the major cause of anemia among adolescent girls [28][29][30]. Numerous studies highlighted that family monthly income [25,[33][34][35][36][37][38], exercise [42,43], meals regularity [25], and respondent education [25] are the societal determinants of anemia in female.…”
Section: Discussionmentioning
confidence: 99%
“…Menstrual disorders not only affect daily activities and quality of life but are also the major cause of anemia among adolescent girls [28][29][30]. Numerous studies highlighted that family monthly income [25,[33][34][35][36][37][38], exercise [42,43], meals regularity [25], and respondent education [25] are the societal determinants of anemia in female.…”
Section: Discussionmentioning
confidence: 99%
“…. Performing adequate aerobic physical activity increases Hb level when accompanied by iron supplementation [15]. Household spending on meat, egg, tofu, rice, vegetables and fruits were not significantly related to anemia.…”
Section: Discussionmentioning
confidence: 86%
“…showed that exercise increased the level RBCs, Hb, and HCT. [ 32 ] The results of another study showed that the body mass index, waist circumference, mean arterial pressure, and diastolic blood pressure significantly decreased after aerobic and resistance exercise but the HDL, fasting plasma glucose, cholesterol, or systolic blood pressure did not change significantly in the exercise groups. [ 33 34 ]…”
Section: Discussionmentioning
confidence: 99%